2013
DOI: 10.1007/s00066-013-0469-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiation with or without induction oxaliplatin plus 5-fluorouracil in locally advanced rectal cancer

Abstract: Short-intense induction FOLFOX-4 significantly improves downstaging and sphincter preservation in low rectal tumors. Long-term outcomes were not improved in the FOLFOX-4 group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…No surgery 2 8 chemotherapy before neoadjuvant CRT or consolidation chemotherapy after neoadjuvant CRT has been proved effective and safe [11,20,21]. In this study, we designed a sandwich-like neoadjuvant regimen combining induction chemotherapy with bevacizumab, concurrent CRT with bevacizumab and consolidation chemotherapy with FOLFOX.…”
Section: Discussionmentioning
confidence: 99%
“…No surgery 2 8 chemotherapy before neoadjuvant CRT or consolidation chemotherapy after neoadjuvant CRT has been proved effective and safe [11,20,21]. In this study, we designed a sandwich-like neoadjuvant regimen combining induction chemotherapy with bevacizumab, concurrent CRT with bevacizumab and consolidation chemotherapy with FOLFOX.…”
Section: Discussionmentioning
confidence: 99%
“…After preoperative chemoradiation, positive CRM rate can vary between 3-14% Kellokumpu et al, 2012;Kenelley et al, 2013;Rullier et al, 2013;Calvo et al, 2014). CRM positivity as high as 26% has been reported in patients with low rectal cancers who undergo APR (Nagtegaal et al, 2002;Bernstein et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative chemoradiation reduces locoregional recurrence but does not alter systemic relapse which is the most common mode of failure in these patients (Gao et al, 2014). Various induction regimens have been developed and administered before chemoradiation in an attempt to reduce distant failure but equivocal outcomes have been reported (Chau et al, 2006;Calvo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Stockholm II trial showed no increased toxicity rate in the radiotherapy group due to the introduction of three- or four-field box techniques [ 9 ]. Furthermore, the reported toxicity is lower than in classically fractionated chemoirradiation, and patient compliance could be increased [ 10 13 ]. The current guidelines allow both modalities, depending on the clinical goal.…”
Section: Introductionmentioning
confidence: 99%